2002
DOI: 10.1038/sj.hdy.6800144
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA diversity in Atherina boyeri populations as determined by RFLP analysis of three mtDNA segments

Abstract: The genetic differentiation and the phylogenetic relationships of eight Atherina boyeri Greek populations have been investigated at the mtDNA level. The populations studied are from two different lakes, a lagoon, the interface zone between the lagoon and the sea, and four marine sites. RFLP analysis of three mtDNA segments (12s rRNA, 16s rRNA and D-loop) amplified by PCR was used. Six, seven and eight restriction enzymes were found to have at least one recognition site at 12s rRNA, 16s rRNA and D-loop respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 39 publications
7
26
0
9
Order By: Relevance
“…All A. boyeri samples, collected within coastal lagoons, turned out to be monophyletic. According to the systematic revision of genus Atherina recently proposed (Klossa-Kilia et al 2002, Trabelsi et al 2002a, our results showed that the 2 individuals of the punctuated and the non-punctuated forms are separate from the other samples, thus provisionally supporting the newly proposed classification. However, before fully accepting this taxonomical revision, an adequate number of samples should be analysed.…”
Section: Relationships Among Atherina Speciessupporting
confidence: 68%
“…All A. boyeri samples, collected within coastal lagoons, turned out to be monophyletic. According to the systematic revision of genus Atherina recently proposed (Klossa-Kilia et al 2002, Trabelsi et al 2002a, our results showed that the 2 individuals of the punctuated and the non-punctuated forms are separate from the other samples, thus provisionally supporting the newly proposed classification. However, before fully accepting this taxonomical revision, an adequate number of samples should be analysed.…”
Section: Relationships Among Atherina Speciessupporting
confidence: 68%
“…A recent study coupling biometric and mitochondrial DNA (mtDNA) data within this species complex, recognized at least three species: A. boyeri, A. punctata and A. lagunae as respectively non-punctuated marine, punctuated marine and lagoon atherines [5,6]. Moreover, molecular investigations by mtDNA [7][8][9][10][11] and allozyme analysis [12] confirmed our previous hypothesis by which A. boyeri can be considered as a complex of two different species (one marine and one living in lagoons and river mouths) [5,6], punctuated fish were not present in all these last studies. The distribution of A. boyeri species sensu stricto ranges in the Northeast Atlantic from the Azores to the Northwest coasts of Scotland; it is common in the Southern North Sea and the English Channel, less so further north, and being found throughout the Mediterranean and Black Sea.…”
Section: Introductionmentioning
confidence: 99%
“…This distinguished punctated (spotted) and non-punctated fishes, as well as those restricted to marine, brackish and freshwater habitats (e.g. Astolfi et al, 2005;Klossa-Kilia et al, 2002;Trabelsi et al, 2002a). Francisco et al (2008) provided a comprehensive phylogenetic analysis of the eastern Atlantic and Mediterranean species of Atherina based on mitochondrial DNA, and revised their taxonomy, proposing three distinct species within the A. boyeri complex: A. boyeri (inhabiting lagoons and freshwater bodies), as well as ''punctuated'' and ''non punctuated'' forms (both typically present in marine conditions).…”
Section: Introductionmentioning
confidence: 99%